Cognitive Dysfunction Among Primi gravidae Attending an Ante Natal Clinic in Kano, Northwest Nigeria (Nigerian Journal of Physiological Sciences, 2019)
Summary: Cognitive deficits among pregnant women have been reported, though the evidence is equivocal. Cognitive dysfunction during pregnancy may have negative consequences on maternal and child health. Yet, very little is known about cognitive function of pregnant women in general and primi gravidae in particular in the area under study. This study aimed to evaluate cognitive function among primi gravidae. About 120 primi gravidae were studied in a large urban hospital in Kano. Mini-Mental State Examination (MMSE) was used to evaluate cognitive function; socio-demographic and clinical data were obtained. Data were processed using IBM SPSS statistics version 20.0. Significant values of P were those < 0.05. The median age of the primi gravidae was 20.0 (3) years; 80 % of them had secondary school education, 88.3 % were in their third trimester of pregnancy and 42.5 % did not have any medical complaints at the time of presentation. The median MMSE score of the primi gravidae was 22.00 (19.0), indicating mild cognitive impairment. Majority of the women (88.3%) had either mild (58.3%) or severe (30%) cognitive dysfunction. The cognitive dysfunction was influenced by level of education (X2 = 11.961, P = 0.003) and type of presenting complaints (X2 = 13.514, P = 0.036). There was significant association between the mild cognitive impairment and level of education (X2 = 11.426, P = 0.022). This study concluded that the primi gravidae had mild cognitive impairment; with majority (88.3%) of them having cognitive dysfunction, which was significantly associated with level of educational attainment and was influenced by the level of education and presenting complaints.